2006
DOI: 10.4161/psb.1.1.2277
|View full text |Cite
|
Sign up to set email alerts
|

At the Root of the Wood Wide Web

Abstract: Arbuscular mycorrhizal (AM) fungi are mutualistic symbionts living in the roots of 80% of land plant species, and developing extensive, below-ground extraradical hyphae fundamental for the uptake of soil nutrients and their transfer to host plants. Since AM fungi have a wide host range, they are able to colonize and interconnect contiguous plants by means of hyphae extending from one root system to another. Such hyphae may fuse due to the widespread occurrence of anastomoses, whose formation depends on a highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(13 citation statements)
references
References 66 publications
0
12
0
1
Order By: Relevance
“… Chen et al (2015a) reported the significant differences in growth traits when plants were grown with the same or opposite sex, and these differences were driven by the N supply. According to Giovannetti et al (2006) , Semchenko et al (2014) , and Xu (2016) , root exudates or mycorrhizal networks should play important roles in neighbor recognition and competition among different plant individuals. In the present study, we found that the growth of male and female P .…”
Section: Discussionmentioning
confidence: 99%
“… Chen et al (2015a) reported the significant differences in growth traits when plants were grown with the same or opposite sex, and these differences were driven by the N supply. According to Giovannetti et al (2006) , Semchenko et al (2014) , and Xu (2016) , root exudates or mycorrhizal networks should play important roles in neighbor recognition and competition among different plant individuals. In the present study, we found that the growth of male and female P .…”
Section: Discussionmentioning
confidence: 99%
“…Volatile organic compounds (VOCs) and green leaf volatiles emitted by stress-exposed plants activate the defense machinery in neighboring plants (Arimura et al, 2000 ; Baldwin et al, 2002 , 2006 ; Matsui, 2006 ; Niinemets et al, 2013 ), and the VOC blend determines the specificity of interplant communications (Ueda et al, 2012 ). Interplant communication is also mediated by common mycorrhizal networks (CMN), which interconnects roots of the same or different plant species (Fitter et al, 1998 ; Giovannetti et al, 2006 ; Selosse et al, 2006 ; Simard et al, 2012 ). CMNs transfer threat information, but also C, N, and P from one plant to another (Leake et al, 2004 ; He et al, 2009 ; Ren et al, 2013 ), thereby promoting plant performance, resource distribution within communities (Eason et al, 1991 ; Selosse et al, 2006 ; He et al, 2009 ; Barto et al, 2012 ) and survival of seedlings on the forest floor (Dickie et al, 2005a , b ; McGuire, 2007 ; Teste et al, 2009 ; Booth and Hoeksema, 2010 ; Bingham and Simard, 2011 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…AMs also enhance plant's defences against the attack from insect herbivores 13 14 . Furthermore, the same or different mycorrhizal hyphae are able to form belowground common mycorrhizal networks (CMNs) interconnecting roots of different plant individuals, species, genera and families in a plant community 15 16 17 . Mycorrhizal networks are able to transfer carbon, nitrogen and phosphorus from one plant to another 18 19 20 , which may have a significant influence on plant performance and resource distribution within plant communities 17 19 .…”
mentioning
confidence: 99%